First‐trimester screening based on cell‐free DNA vs combined screening: A randomized clinical trial on women's experience. (13th August 2020) - Migliorini, Sonia; Saccone, Gabriele; Silvestro, Fiora; Massaro, Giulia; Arduino, Bruno; D'Alessandro, Pietro; Petti, Maria Teresa; Paino, Jessica Anna Cinzia; Guida, Maurizio; Locci, Mariavittoria; Zullo, Fulvio
Abstract: Objective: To compare women's experience of first‐trimester combined screening (FTCS), with women's experience of an approach that uses the combination of a detailed early anatomy scan and cell‐free DNA (cfDNA) analysis. Methods: This was single‐center, open label, parallel group, randomized clinical trial. Pregnant women were randomized at the time of their first prenatal visit to either a policy of first‐trimester risk assessment based on FTCS, or to a policy of first‐trimester risk assessment based on ultrasound findings and cfDNA. FTCS included ultrasound evaluation with crown‐rump length, nuchal translucency (NT) measurement, and a detailed ultrasound scan, along with biochemistry (PAPP‐A and free beta hCG). In this group, invasive diagnostic testing was offered to patients with risk >1 in 100, or NT >3.5 mm, or any fetal abnormalities on ultrasound. Women randomized in the intervention group received an approach of first‐trimester risk assessment based on ultrasound findings and cfDNA. cfDNA analysis included a simultaneous microarray‐based assay of non‐polymorphic (chromosomes 13, 18, 21, X and Y) and polymorphic loci to estimate chromosome proportion and fetal fraction. In the intervention group, invasive diagnostic testing was offered to patients with abnormal cfDNA screening results, or NT >3.5 mm, or any fetal abnormalities on ultrasound. Participants received pre‐test and post‐test questionnaires regarding to measure reassurance, satisfaction, and anxiety. The primary outcome was the post‐test reassurance, defined as mean score of reassurance post‐test questionnaire. The effect of the assigned screening test on the mean of each outcome was quantified as mean difference (MD) with 95% confidence interval (CI). Results: Forty women with singleton gestations were enrolled in the trial. Mean score for reassurance was significantly higher in the cfDNA group compared to the FTCS group in the pre‐test questionnaire (MD 0.80 points, 95% CI 0.27 to 1.33) and in the post‐test questionnaire (MD 16.50 points, 95% CI 2.18 to 30.82). Women randomized to the cfDNA group had higher satisfaction and lower mean anxiety score as assessed in the STAI pre‐test questionnaire. Conclusions: First‐trimester risk assessment for fetal aneuploidy with a combination of a detailed ultrasound examination and cfDNA is associated with better maternal reassurance and better maternal satisfaction compared to the standard first‐trimester combined screening with nuchal translucency, and biochemistry. Trial registration: Clinicaltrials.gov NCT04077060.